Komunikasi Antar Umat Beragama di Kota Palopo (Perspektif Kajian Dakwah) - Masmuddin Masmuddin (LP2M IAIN Palangka Raya, 2017)
Islam is a dakwah religion, that obliges all adherents to convey the messages of the teachings contained in it as a life guidance. Therefore, all Muslims should convey the teachings of Islam to all mankind in a good way according to the instructions of the Qur'an and the Prophet Muhammad’s life style. Inter-religious communication in Palopo have been going well but do not reach the very satisfying point yet which is caused by several factors such as the lack of dialogue conducted by the followers of religious communities. Of course, they do it sometimes, but it is not intensive. This occurs because many religious leaders get busy, and even there are still people who consider that inter-religious communication is not necessary. In the perspective of dakwah, inter-religious communication is a must because Islam is the religion that was gifted to the Prophet Muhammad, by Allah, for all mankind because Islam is for all. Therefore, all people need to listen to and understand any information about Islam. Eventhough Islam itself must not be imposed to all mankind.